2017
DOI: 10.3171/2016.2.jns152173
|View full text |Cite
|
Sign up to set email alerts
|

RNF213 as the major susceptibility gene for Chinese patients with moyamoya disease and its clinical relevance

Abstract: OBJECTIVE Moyamoya disease (MMD) is a rare, genetically heterogeneous cerebrovascular disease. The authors conducted a genetic study of really interesting new gene (RING) finger protein 213 ( RNF213); actin alpha 2 ( ACTA2); BRCA1/BRCA2-containing complex subunit 3 ( BRCC3); and guanylate cyclase 1, soluble, alpha 3 ( GUCY1A3) as well as a clinical phenotype analysis in Chinese MMD patients to determine whether genetic differences are responsible for the different clinical features that appear in MMD in differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 29 publications
(51 reference statements)
1
58
3
Order By: Relevance
“…Moreover, patients with a family history of MMD were more likely to carry the p.R4810K variant in the current study, and this result supported the results of some previous studies. 1,2,20 Interestingly, the ages of patients with family history were largely concentrated in the 5-9 age range, and these results coincided with that of Zhang et al, 21 who found that Chinese familial MMD can occur in patients and their third-degree relatives, of which firstdegree relatives are the most affected. Doctors should pay more attention to the family histories of patients with MMD during the process of diagnosis and expand the scope of screening in high-risk groups, especially younger patients.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, patients with a family history of MMD were more likely to carry the p.R4810K variant in the current study, and this result supported the results of some previous studies. 1,2,20 Interestingly, the ages of patients with family history were largely concentrated in the 5-9 age range, and these results coincided with that of Zhang et al, 21 who found that Chinese familial MMD can occur in patients and their third-degree relatives, of which firstdegree relatives are the most affected. Doctors should pay more attention to the family histories of patients with MMD during the process of diagnosis and expand the scope of screening in high-risk groups, especially younger patients.…”
Section: Discussionsupporting
confidence: 82%
“…The p.R4810K variant in RNF213 was identi ed as a founder variant with a strong susceptibility in MMD patients [15]. The p.R4810K mutation was found in 31.4% MMD patients in China [14], 75.8% MMD patients in Korea [16], and 95.1% MMD patients in Japan [10]. In present study, the incidence of p.R4810K variant in hemorrhagic MMD was 19.2%, which was much lower than the overall incidence.…”
Section: Discussioncontrasting
confidence: 46%
“…MMD was diagnosed according to the Japanese guidelines published in 2012 [13]. Patients who met the following criteria were included in this study: 1) p.R4810K variant was sequenced [14]. 2) Digital subtraction angiography (DSA) was received.…”
Section: Patients Datamentioning
confidence: 99%
“…In our results, we found that RNF213 4810G > A (rs112735431) and 4950G > A (rs371441113) increased the likelihood of anterior ICASO. Both of these variants have been reported to be significantly associated with MMD in Korean and Chinese populations [18,21,40,41]. Similarly, there was a study of 221 Japanese patients, which found that RNF213 4810G > A was significantly associated with anterior ICASO but not posterior ICAS [42].…”
Section: Discussionmentioning
confidence: 86%